Intracellular Localization of the ABCC Proteins of Leishmania and Their Role in Resistance to Antimonials - Leprohon, Philippe (American Society for Microbiology (ASM), 2009)
The ABCC subfamily of proteins is composed of nine members in Leishmania. We report that all of these proteins have an intracellular localization and that the overexpression of at least four members, ABCC3, ABCC4, ABCC5, and ABCC7, can confer resistance to antimonials, the first-line drug against Leishmania.